2006
DOI: 10.4049/jimmunol.176.9.5607
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Mediated Remodeling and Fibrinolytic Activity Protect against Fatal Glomerulonephritis

Abstract: Mast cells are detrimental in several inflammatory diseases; however, their physiological roles are also increasingly recognized. Recent data suggest that mast cells may also be involved in renal diseases. We therefore used congenitally mast cell-deficient W/Wv mice and normal +/+ littermates to assess their role in anti-glomerular basement membrane-induced glomerulonephritis. Following administration of anti-glomerular basement membrane Abs, W/Wv mice exhibited increased mortality as compared with +/+ mice ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 74 publications
2
49
2
Order By: Relevance
“…Compelling evidence suggests that renal dysfunction in different forms of AKI is the outcome of secretion of immune mediators [5][6][7][8][9] and the activation of renal resident and recruited leukocytes 2,3,10,11 ; however, recent studies also suggested that certain cytokines 40 -43 and immune cells 23,44,45 may limit kidney injury by reducing the immune-mediated inflammatory response. 46 During renal injury, DCs are thought to contribute to renal inflammation and exacerbate kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that renal dysfunction in different forms of AKI is the outcome of secretion of immune mediators [5][6][7][8][9] and the activation of renal resident and recruited leukocytes 2,3,10,11 ; however, recent studies also suggested that certain cytokines 40 -43 and immune cells 23,44,45 may limit kidney injury by reducing the immune-mediated inflammatory response. 46 During renal injury, DCs are thought to contribute to renal inflammation and exacerbate kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…With the association of mast cells and T regulatory cells already established, 109 one study suggested that systemic mast cells infiltrate local lymphoid organs and activate regulatory T cells to confer protection. 123 Kanamaru et al 124 attributed the beneficial outcome of mast cellcompetent mice to improved repair function in the kidney. In a model of autoimmune immune complex disease, the absence of mast cells facilitated an altered pattern of disease but did not alter the severity of injury.…”
Section: Role Of Mast Cells In Inflammatory and Autoimmune Kidney Dismentioning
confidence: 99%